2021
DOI: 10.1111/codi.15812
|View full text |Cite
|
Sign up to set email alerts
|

A novel bowel rehabilitation programme after total mesorectal excision for rectal cancer: the BOREAL pilot study

Abstract: Aim Low anterior resection syndrome (LARS) following sphincter‐preserving surgery for rectal cancer has a high prevalence, with an impact on long‐term bowel dysfunction and quality of life. We designed the bowel rehabilitation programme (BOREAL) as a proactive strategy to assess and treat patients with LARS. The BOREAL programme consists of a stepwise approach of escalating treatments: medical management (steps 0–1), pelvic floor physiotherapy, biofeedback and transanal irrigation (step 2), sacral nerve neurom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 38 publications
1
36
0
Order By: Relevance
“…Patients with major LARS at 3-to 6-months are likely to continue to suffer persisting dysfunction. The bowel rehabilitation programme (BOREAL) pilot programme has demonstrated that ''preventative'' care can be instituted on discharge (with bowel continuity) for all patients undergoing rectal resection, 48 but few institutions have such a programme. Therefore, these data suggest that all patients should have a functional follow-up assessment between 3 and 6 months and those with major LARS should have more intensive supportive care instituted with escalation as required.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with major LARS at 3-to 6-months are likely to continue to suffer persisting dysfunction. The bowel rehabilitation programme (BOREAL) pilot programme has demonstrated that ''preventative'' care can be instituted on discharge (with bowel continuity) for all patients undergoing rectal resection, 48 but few institutions have such a programme. Therefore, these data suggest that all patients should have a functional follow-up assessment between 3 and 6 months and those with major LARS should have more intensive supportive care instituted with escalation as required.…”
Section: Discussionmentioning
confidence: 99%
“…26 There are now a variety of treatments that might benefit patients, such as pelvic floor physiotherapy and sacral nerve stimulation. 27 These interventions could improve long-term quality of life for PRMS survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Up to 80% of patients following surgery for rectal cancer report symptoms when this assessment tool is used and it may be that more focused questioning of PRMS survivors would uncover morbidity due to unpredictability and frequency of bowel motions 26 . There are now a variety of treatments that might benefit patients, such as pelvic floor physiotherapy and sacral nerve stimulation 27 . These interventions could improve long‐term quality of life for PRMS survivors.…”
Section: Discussionmentioning
confidence: 99%
“…The BOREAL programme [ 8 ] consists of five sequential therapeutic steps starting from an approach as conservative as possible and up to surgery. The first one is medical management (steps 0–1), in case of persistence of symptomatology, the patients undergo pelvic floor physiotherapy, biofeedback and transanal irrigation (step 2), sacral nerve neuromodulation (step 3), percutaneous endoscopic cecostomy and anterograde enema (step 4), definitive colostomy (step 5).…”
Section: Methodsmentioning
confidence: 99%